2013
DOI: 10.1177/1352458513506503
|View full text |Cite
|
Sign up to set email alerts
|

Oligoclonal bands and age at onset correlate with genetic risk score in multiple sclerosis

Abstract: Background Many genetic risk variants are now well established in multiple sclerosis (MS), but the impact on clinical phenotypes is unclear. Objective To investigate the impact of established MS genetic risk variants on MS phenotypes, in well-characterized MS cohorts. Methods Norwegian MS patients (n = 639) and healthy controls (n = 530) were successfully genotyped for 61 established MS-associated single nucleotide polymorphisms (SNPs). Data including and excluding Major Histocompatibility Complex (MHC) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 28 publications
7
43
1
2
Order By: Relevance
“…Several studies addressed the role of HLA allelic isoforms on the MS phenotype, the most replicated being the association between HLA-DRB1*15:01 and earlier disease onset, 6,8,10,26,27 followed by the predominance of female patients 7,28 and the positivity of oligoclonal bands. 28,29 The HLA alleles and SNPs included for analysis in the present study were originated from the most recent study of the International Multiple Sclerosis Genetics Consortium 5 in which HLA alleles were statistically imputed from a large, high-density SNP data set.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies addressed the role of HLA allelic isoforms on the MS phenotype, the most replicated being the association between HLA-DRB1*15:01 and earlier disease onset, 6,8,10,26,27 followed by the predominance of female patients 7,28 and the positivity of oligoclonal bands. 28,29 The HLA alleles and SNPs included for analysis in the present study were originated from the most recent study of the International Multiple Sclerosis Genetics Consortium 5 in which HLA alleles were statistically imputed from a large, high-density SNP data set.…”
Section: Discussionmentioning
confidence: 99%
“…57 Another study confirmed interactions involving pairs of HLA class II alleles: DQA1*01:01-DRB1*15:01 and DQB1*03:01-DQB1*03:02, with a protective effect in MS. 61 In the same study, HLA class I-mediated protection has also been observed for HLA-A*02:01, HLA-B*44:02, HLA-B*38:01 and HLA-B*55:01. 61 More recently, HLA-B*44-mediated protection was also reported in MS. 62 Similarly, an imputation study revealed protection by the high-resolution HLA-B*44:02 genotype in MS. 63 Finally, HLA-B*44:02 was observed in LD with HLA-C*05, which independently demonstrated protection for MS in the absence of DRB1 risk alleles; 64 thus, it is challenging to discriminate whether these observations reflect a single effect through strong LD.…”
Section: Hla and Multiple Sclerosismentioning
confidence: 99%
“…At the present time, we can state that the wGRS has a low predictive power and clinical utility 3,8,9,13 and we believe that a composite score is needed including different parameters and different layers of data for a clinical application.…”
Section: Discussionmentioning
confidence: 95%